2005
DOI: 10.1111/j.1523-1755.2005.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-enhanced MRI as a diagnostic and prognostic biomarker of sepsis-induced acute renal failure in aged mice

Abstract: Dendrimer-enhanced MRI is a novel biomarker that provides information for the early diagnosis, drug responsiveness, and prognosis of sepsis-induced ARF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 26 publications
5
50
0
1
Order By: Relevance
“…Because volume resuscitation can reverse LPS-induced renal injury in aged mice (34), we added volume resuscitation and antibiotic treatment to the standard CLP model. Animals became clinically ill at 5-6 hours after surgery, at which time they had evidence of liver damage; kidney damage was evident by MRI early (62), but serum creatinine and BUN levels did not significantly increase until 12 hours after surgery (63). With these additions, consistent histological renal damage with significant increase in serum creatinine were observed, not because fluids and antibiotics were harmful to the kidney, but because the animals could survive long enough to develop AKI (34,64).…”
Section: Stent Peritonitis [Casp]); and (C) Infusion Or Instillation mentioning
confidence: 99%
“…Because volume resuscitation can reverse LPS-induced renal injury in aged mice (34), we added volume resuscitation and antibiotic treatment to the standard CLP model. Animals became clinically ill at 5-6 hours after surgery, at which time they had evidence of liver damage; kidney damage was evident by MRI early (62), but serum creatinine and BUN levels did not significantly increase until 12 hours after surgery (63). With these additions, consistent histological renal damage with significant increase in serum creatinine were observed, not because fluids and antibiotics were harmful to the kidney, but because the animals could survive long enough to develop AKI (34,64).…”
Section: Stent Peritonitis [Casp]); and (C) Infusion Or Instillation mentioning
confidence: 99%
“…This may be another indication that different pathways mediate injury in the liver as compared with the kidney (6) or may represent a type 2 statistical error secondary to the insensitivity of transminase enzymes at detecting liver dysfunction. However, using mice lacking the protein MyD88 we previously demonstrated that the degree of liver injury (as measured by AST and ALT) does not correspond with sepsis mortality but renal injury closely predicted survival (6,10). Therefore, we believe it is an important finding that anti-CD147 prevented ARF even in the absence of a significant effect on liver injury.…”
Section: Discussionmentioning
confidence: 91%
“…Twenty contiguous coronal T2-weighted fast-spin echo images (echo train length 4) of 0.5-mm slice thickness were collected with the following parameters: repetition time (TR) ϳ2,500 ms depending on respiration rate; effective echo time ϭ 36 ms; field of view ϭ 20 mm ϫ 20 mm; matrix ϭ 256 ϫ 256; 6 signal averages; total scan time was ϳ16 min. Gadolinium-based G4 dendrimer intravenous contrast was used as described (15). Briefly, a single coronal slice (1-mm thick) through the center of both kidneys was acquired using a Fast Low Angle Shot (FLASH) pulse sequence with the following parameters: repetition time 40 ms, echo time 3.16 ms, Flip angle 30°, field of view 40 ϫ 40 mm, matrix 256 ϫ 256, 4 signal averages.…”
Section: Response To Bumetanide Hsd11b2mentioning
confidence: 99%